PROBLEM BASED LEARNING IMPLEMENTATION IN PAI LEARNING - Nurman Ginting (Proceeding International Seminar of Islamic Studies, 2021)
The aim of this PAI must of course be accompanied by changes in several models, strategies, methods, and approaches in presenting conventional Islamic Studies material. The Problem Based Learning learning model is one of the many learning models that can be implemented in Islamic Education learning that can help the learning process of students in understanding Islamic Education materials taught in schools. Contextually Problem Based Learning equips students in solving long-term life problemsKeyword: Implementation, Problem Based Learning, PAI